Katherine Mansfield and the Modernist Marketplace - McDonnell, J. author. aut Link
IX, 220 p.
Keywords: Katherine Mansfield had a career-long engagement with the literary marketplace from the age of eighteen. This book examines how she developed as a writer within a range of book and periodical publishing contexts, reconsidering her writing's enactment of a commercially viable modern aesthetic in her experimentation with the short story form.